2014
DOI: 10.1007/978-3-662-45501-2_18
|View full text |Cite
|
Sign up to set email alerts
|

Towards Actionable Business Intelligence: Can System Dynamics Help?

Abstract: Abstract. Business intelligence (BI) and data analytics provide modern enterprises with insights about internal operations, performance, as well as environmental trends, and enable them to make data-driven decisions. Insights resulting from these systems often suggest several alternative changes or corrective actions within the enterprise. In this context, to trade-off and find the most proper action(s) is a non-trivial task due to existing dynamics and complexities of the enterprise. This paper proposes a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The coding revealed that most of the work in SD-EE is conceptual and focused on the design phase. The SD models being proposed still need to be validated and redefined, with most models only being tested for feasibility on fictitious demonstration case studies (Fayoumi and Loucopoulos, 2016;Golnam et al, 2010;Nalchigar et al, 2014;Roychoudhury et al, 2014a). Although consistency in the content of the research work is observed, there is scope for further development through implementation in the industry.…”
Section: Jm2mentioning
confidence: 99%
“…The coding revealed that most of the work in SD-EE is conceptual and focused on the design phase. The SD models being proposed still need to be validated and redefined, with most models only being tested for feasibility on fictitious demonstration case studies (Fayoumi and Loucopoulos, 2016;Golnam et al, 2010;Nalchigar et al, 2014;Roychoudhury et al, 2014a). Although consistency in the content of the research work is observed, there is scope for further development through implementation in the industry.…”
Section: Jm2mentioning
confidence: 99%
“…Nalchiger et al, in a research they conducted in 2014, presented an approach based on systems dynamics modeling to support decisions and choose the best alternative actions for the organization through the outputs of the business intelligence system. These researchers modeled the results of the business intelligence system with the decision-making process in the organization and actually presented a combination of business intelligence and a decision support system [45] .…”
Section: Associated Workmentioning
confidence: 99%